The impact of generic medicines on the European pharmaceutical market: The example of Poland - Matsuieva, Julia (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In this paper has been done a review of the existing situation on European pharmaceutical market. It was found that the Polish pharmaceutical market is quite different from other countries of the European Union. The share of generic medicines in Poland is the highest in the European Union. Quantitatively about 85% of the pharmaceutical market is composed of generic drugs. The social role of generics is expressed in their accessibility, affordable price, diversity and security for the most vulnerable part of the population — people with various health problems. It is impossible to overestimate the importance of generic medicines in both saving of the state’s budgets and the rational use of public finances
Keywords: leki generyczne; monopol; konkurencja; leki opatentowane; dostęp do rynku; wartość społeczna